2019
DOI: 10.1038/s41467-019-08587-2
|View full text |Cite
|
Sign up to set email alerts
|

Ripplocations provide a new mechanism for the deformation of phyllosilicates in the lithosphere

Abstract: Deformation in Earth’s lithosphere is localised in narrow, high-strain zones. Phyllosilicates, strongly anisotropic layered minerals, are abundant in these rocks, where they accommodate much of the strain and play a significant role in inhibiting or triggering earthquakes. Until now it was understood that phyllosilicates could deform only by dislocation glide along layers and could not accommodate large strains without cracking and dilation. Here we show that a new class of atomic-scale defects, known as rippl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…The presence of these discrete muscovite‐ and chlorite‐rich planes promoted connectivity between weak phyllosilicate grains that strongly localized deformation and weakened the rock (Bukovská et al, 2016; Ceccato et al, 2018; Hunter et al, 2016; Mariani et al, 2006; Menegon et al, 2008; Shea & Kronenberg, 1993; Wintsch et al, 1995). Finally, the presence of such phyllosilicate‐rich planes can accommodate large amount of strain, through the new mechanism of ripplocation motion (i.e., the motion of a new type of crystal defect—ripplocation—that involves a ripple of the basal layer and a basal dislocation, where the ripple enables c ‐axis parallel deformation in phyllosilicates; Kushima et al, 2015) rather than dislocation glide, as recently suggested by Aslin et al (2019).…”
Section: Discussionmentioning
confidence: 87%
“…The presence of these discrete muscovite‐ and chlorite‐rich planes promoted connectivity between weak phyllosilicate grains that strongly localized deformation and weakened the rock (Bukovská et al, 2016; Ceccato et al, 2018; Hunter et al, 2016; Mariani et al, 2006; Menegon et al, 2008; Shea & Kronenberg, 1993; Wintsch et al, 1995). Finally, the presence of such phyllosilicate‐rich planes can accommodate large amount of strain, through the new mechanism of ripplocation motion (i.e., the motion of a new type of crystal defect—ripplocation—that involves a ripple of the basal layer and a basal dislocation, where the ripple enables c ‐axis parallel deformation in phyllosilicates; Kushima et al, 2015) rather than dislocation glide, as recently suggested by Aslin et al (2019).…”
Section: Discussionmentioning
confidence: 87%
“…5 c showing (marked by the red arrow) the vertical orientation of the graphitic lattice planes might be related to the formation of nanofolds (inset of Fig. 5 c) alongside the film due to an excess of uncompensated tangential stress 30 , 61 , 62 . Under high-resolution TEM, these nanofolds 30 revealed a crystalline orientation that differed from the rest of the NGF area; graphitic lattice basal planes were almost vertically oriented instead of horizontally, as in the rest of the thin film (inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thouless et al, 1987). This mechanism bears an indirect resemblance to the recently proposed mechanism of phyllosilicate deformation via migration of so-called ripplocations where delamination of phyllosilicate layers occurs to release layer normal elastic strain (Aslin et al, 2019). We ignore the resistance offered by comminution or plastic bending of the cleaved-off basal slivers as the mechanical work needed to drive these processes is small (see Text S1 in the supporting information).…”
Section: Microstructural Modelmentioning
confidence: 92%